2014
DOI: 10.5114/pg.2014.46168
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibroma of the stomach without Recklinghausen’s disease: a

Abstract: Neurofibromas of the stomach can occur in the course of Recklinghausen's disease. Sporadic gastric neurofibroma appears rarely. This tumour may look like an ulcer and can be a cause of abdominal pain, nausea, and bleeding from the gastrointestinal tract. We reported a 61-year-old women complaining of stomachache for several months. Gastroscopy revealed a tumour with ulceration in the prepyloric part of the stomach. Helicobacter pylori infection was also present. Helicobacter pylori eradication and prolonged tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
1
Order By: Relevance
“…NSE is an isoenzyme specifically secreted by central neurons and neuroendocrine cells, which participates in the metabolic processes of nerve cells and maintains the normal physiological function of the nervous system. NSE is positive in solitary GN as reported by Madro et al 3 Of the patients, 45.5% were positive for NSE in our study, which further confirmed that the lesion was neurogenic. Positive NSE, S-100 protein, cannot predict prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…NSE is an isoenzyme specifically secreted by central neurons and neuroendocrine cells, which participates in the metabolic processes of nerve cells and maintains the normal physiological function of the nervous system. NSE is positive in solitary GN as reported by Madro et al 3 Of the patients, 45.5% were positive for NSE in our study, which further confirmed that the lesion was neurogenic. Positive NSE, S-100 protein, cannot predict prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Solitary neurofibroma is a local single tumor without other manifestations of NF, often presenting different clinical manifestations because of its occurrence in different locations. 3 To date, solitary neurofibroma has been reported in the oral cavity, 4 mandible, 5 parotid gland, 6 penis, 7 spermatic cord, 8 infratemporal fossa, 9 abdominal wall, 10 gallbladder, 11 bile duct, 12 esophagus, 13 colon, 14 etc. However, the studies on solitary gastric neurofibroma (GN) consist only individual case reports, with little data and little usable information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal neurogenics derive from different components of nerve fibers, mostly autonomic components of Auerbach's plexus [ 4 ]. They consist 5% of nonepithelial gastric tumors and are mostly benign with 10% malignant transformation risk [ 5 , 6 ]. Schwannoma, neurofibroma, and granular cell tumors are their subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Шванома шлунка була впер-ше описана на початку ХХ століття H. Verocay. Шваноми (невриноми, неврилемома) шлунка зустрічаються дуже рідко, здебільшого є проявом хвороби Реклінхаузена [13] та вкрай рідко -спорадичною хворобою. За даними різних авторів, вони становлять близько 0,2% всіх пухлин шлунка і близько 4% доброякісних пухлин шлунка [3].…”
Section: оглядиunclassified